Scrutinizing English Academic Writing Skills: Indonesian Postgraduate Students' Challenges and Strategies in an AI-Empowered Era - Andika, Jeffri Dian; Waly, Muchamad Muchibbuddin; Yulia, Yuyun; Reswari, Girindra Putri Ardana (Journal of Languages and Language Teaching, 2025)
Indonesian postgraduate students encounter significant challenges in academic writing, particularly in areas such as clarity, coherence, organization, grammar, and plagiarism prevention. This study investigates these challenges and explores the potential of AI-driven strategies to enhance writing skills. Utilizing a mixed-methods approach, including quantitative surveys of 50 participants and qualitative interviews with six postgraduates, the research identified key obstacles such as difficulty in formulating clear research questions, using precise academic vocabulary, maintaining logical flow, and mastering citation practices. To address the issues, they employed several effective strategies employed      including seeking feedback, attending workshops, outlining, varying sentence structures, and thorough proofreading. AI tools like Grammarly, QuillBot, ChatGPT, and Mendeley are widely used for grammar checks, paraphrasing, citation management, and enhancing coherence, demonstrating their value in supporting academic writing. However, the study underscores the importance of human oversight to ensure originality and foster critical thinking. These findings have implications for both theoretical advancement and educational practice, particularly in the integration of AI tools in higher education. The findings hold significant implications for educational practice, suggesting that AI integration in higher education can serve as an effective support tool, provided it is accompanied by guidance on responsible usage.